Current status of hepatitis C virus among people living with human immunodeficiency virus in Egypt. (24th November 2021) - Elsharkawy, Aisha; Alem, Shereen Abdel; Cordie, Ahmed; Mohamed, Rahma; Meshaal, Safa; Esmat, Gamal
Abstract: Background: Human immunodeficiency virus (HIV)–hepatitis C virus (HCV) co-infection is increasing due to their similar routes of transmission. Co-infection poses a big challenge. Information on the prevalence of HCV infection in Egyptian HIV individuals is scarce. Methods: A cross-sectional study was conducted on 1004 HIV individuals who were recruited from July 2018 to March 2019. Blood samples obtained from HIV individuals were subsequently screened for HCV antibodies using the Murex anti-HCV (version 4) enzyme-linked immunosorbent assay test. HCV RNA was performed only on anti-HCV antibody–positive samples. Logistic regression was used to identify factors associated with HCV seroprevalence using SPSS (IBM, Armonk, NY, USA). Results: Among 1004 participants, 349 exhibited a positive result for anti-HCV antibodies (34.8% [95% confidence interval 31.81 to 37.8]). The most commonly self-reported risk factor of HIV infection by the co-infected participants was intravenous drug use (IDU) (303/349 [86.8%]). In multinomial analysis, risk factors identified as statistically associated with HCV seroprevalence include IDU, history of surgical operations and dental procedures and HIV viral load (p<0.001, 0.032, <0.001 and 0.006, respectively). Under combination antiretroviral therapy (cART), the proportion of HIV mono-infected individuals with an undetectable HIV viral load was significantly higher than those with co-infection (p<0.0007). We also found that HIV–HCV co-infected participants exhibited significantly higher CD4 + cell counts than those with HIV mono-infection (p=0.04). Conclusions: The prevalence of HIV–HCV co-infection is higher in Egypt compared with other countries in Africa. It is essential to screen all HIV-infected patients for HCV infection for early identification, counselling and initiation of anti-HCV treatment.